Evaluation of in vitro pharmacological activities of medicinal mushrooms in the context of dry eye disease - Areesanan, Alexander; Wasilewicz, Andreas; Nicolay, Sven; Grienke, Ulrike; Zimmermann-Klemd, Amy M.; Rollinger, Judith M.; Gründemann, Carsten (Frontiers in Pharmacology, 2025)
IntroductionEthnic groups worldwide use mushrooms, particularly polypores (a group of fungi with woody fruiting bodies), to manage inflammatory conditions. In this study, the in vitro anti-inflammatory potential and mycochemical composition of six polypore extracts derived from the fruit bodies of Fomes fomentarius (L.) Fr. (FF), Ganoderma lucidum (Fr.) P. Karst. (GL), Ganoderma tsugae Murrill (GT), Gloeophyllum odoratum (Wulfen) Imazeki (GO), Laricifomes officinalis (Vill.) Kotl. and Pouzar (LO), and the sclerotium of Inonotus obliquus (Fr.) Pilát (IO) were analyzed for their relevance to treat dry eye disease (DED).MethodsEthanolic extracts of the fungal materials were prepared and chemically characterized by UHPLC-ELSD/MS and TLC analyses before investigating the extracts’ cytotoxic, antioxidant, anti-inflammatory, and lipid-stimulating properties. Radical scavenging and intracellular reactive oxygen species (ROS) assays were carried out in UVB-exposed human corneal epithelial (HCE-T) and immortalized human meibomian gland epithelial (IHMGEC) cells to evaluate antioxidant capacities. To examine the influence of the extracts of the inflammatory processes, associated with DED, a secretion assay for pro-inflammatory cytokines was conducted in UVB-exposed HCE-T and LPS-stimulated monocytic THP-1 cells. The lipid droplets secreted by IHMGECs were analyzed to determine the extracts’ lipid-stimulating properties.ResultsExtracts of GT, GL, GO, and IO found to have high radical scavenging abilities. They significantly reduced intracellular ROS in UVB-exposed HCE-T and iHMGEC cells. GO and GL extracts inhibited cytokine secretion in HCE-T cells even at low concentrations. All tested extracts significantly inhibited the secretion of pro-inflammatory cytokines (IP10, IL-6, IL-8, and α) in LPS-stimulated monocytic THP-1 cells.ConclusionSeveral extracts of the investigated fungal materials exhibit multifaceted pharmacological in vitro activities. Due to low cytotoxic activity on HCE-T, iHMGEC, and THP-1 cells, extracts from GL and GO are particularly pertinent to the treatment of DED, even at low concentrations.